International Technical Digest on Electron Devices Meeting 1992
DOI: 10.1109/iedm.1992.307507
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional characterization of bipolar transistors in a submicron BiCMOS technology using integrated process and device simulation

Abstract: Results of complete 3-dimensional ac/dc characterizations of the npn transistor in a submicron BiCMOS technology are presented. Accuracy and throughput acceptable for constructing compact models is achieved through the use of multidimensional process simulation, adaptive grid generation and preconditioned iterative techniques for both dc and small-signal analysis. Comparisons of 2-and 3-dimensional simulations with measurements enable assessments of the magnitude of 3-dimensional effects, thereby suggesting ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Such capabilities make it a particularly suitable numerical tool for continuum-based modeling of nonequilibrium transport and equilibrium electrostatics in bioelectrical systems. Previously, PROPHET has been used extensively in the modeling and simulation of semiconductor-based processes (15) and devices (16). It has recently been applied to solving coupled PoissonNernst-Planck equations in the modeling of charge transport in ompF porin ion channels (17).…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Such capabilities make it a particularly suitable numerical tool for continuum-based modeling of nonequilibrium transport and equilibrium electrostatics in bioelectrical systems. Previously, PROPHET has been used extensively in the modeling and simulation of semiconductor-based processes (15) and devices (16). It has recently been applied to solving coupled PoissonNernst-Planck equations in the modeling of charge transport in ompF porin ion channels (17).…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Simulations based on the PROPHET code [11] showed that the deep S/D implants do not affect the effective channel length. The 30 mV shift observed in the 21 Å gate oxide devices was obtained in simulations by "implanting" approximately cm B atoms into the channel area.…”
Section: Discussionmentioning
confidence: 98%
“…Fig. 1 depicts the numerically simulated [12], [13] hole concentration in a bipolar transistor in the low injection regime of operation. The simulated hole concentration in the quasi-neutral base regions of the indium-implanted transistor is about a factor of 8-10 lower than the boron-implanted transistor due to the impurity freeze-out effect [see also (1)].…”
mentioning
confidence: 99%